Model of Process Management System in Enterprises of the Hard Coal Mining Industry - Bijańska Jolanta; Wodarski Krzysztof (Management Systems in Production Engineering, 2020)
The primary objective of this paper is to present a model of a process management system developed to support the restructuring of Polish enterprises of the hard coal mining industry. The development of this model required research in three stages using several research methods. The stage I of the research was oriented towards the recognition of the existing state of knowledge in the scope of previously developed models of process management in enterprises. At this stage, a method of reviewing the literature, the analysis and synthesis of the results of considerations, was used. The stage II was oriented towards presenting of the current state of knowledge in the field of process management to the managerial staff of mines in order to identify their needs, capabilities and preferences. The research were attended by 24 managers from PGG SA and JSW SA. At this stage, the method of targeted free-form interview and discussions, was used. The stage III of the research was oriented towards the development of a process management system model in enterprises operating in the hard coal mining industry, based on the scientific achievements to date in the field of process management and consensus on the needs, preferences and capabilities of mine managerial staff with regard to its specific elements. At this stage, the method of analysis and synthesis was used. The results of the research presented in this publication are primarily addressed to the managerial staff of polish hard mines, as they provide a synthesized response to the problem of the lack of consistent process management guidelines that could set a standard within a mining enterprise. The model presented in the publication is of a general nature, although it may provide a basis for the application of process management for mines.